2018
DOI: 10.29252/wjps.7.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pistacia Atlantica Resin Oil on Anti-Oxidant, Hydroxyprolin and VEGF Changes in Experimentally-Induced Skin Burn in Rat

Abstract: BACKGROUNDSevere burn damage and its consequences are life threatening which can complicate patients’ health. Medicinal and traditional plants are considered as safe, natural and inexpensive source of treatment for wide variety of diseases. This study assessed beneficial effect of Pistacia atlantica oil on rats burn wound healing and its potential effects on malondialdehyde (MDA), vasculoendothelial growth factor (VEGF), hydroxyprolin and antioxidant status in wound area.METHODSThirty male rats weighing 200±10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Moist exposed burn ointment is an oil-based ointment composed of sesame oil and some other plant ingredients. 10,11,[14][15][16] However, in our study, the simple dressing which was a combination of a sterile gauze and normal saline did not show any significant improvement in burn wounds. Therefore, the moisture alone is not a factor for improvement of burn wounds.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Moist exposed burn ointment is an oil-based ointment composed of sesame oil and some other plant ingredients. 10,11,[14][15][16] However, in our study, the simple dressing which was a combination of a sterile gauze and normal saline did not show any significant improvement in burn wounds. Therefore, the moisture alone is not a factor for improvement of burn wounds.…”
Section: Discussionmentioning
confidence: 73%
“…Herbal products such as moist exposed burn ointment, Aloe vera, Aloe littoralis, Aloe saponaria haw and green tea have been effective in treatment of burn injuries in animal models. [10][11][12][13][14][15][16][17][18]28,29 On the other hand, using stem cells or skin grafts in burn injuries is costly and limited for developing countries, therefore, alternative therapies for second degree burn wounds has become a reasonable modality for cure. 30 Our results showed that M. pulegium extract was beneficial in treating second degree burn injuries, but the side effects of this product are not yet determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreas samples of animals were sonicated and homogenized by Ultrasonic Processor (Hielscher, UP200H) in cold PBS with pH=7.4. The homogenized samples were centrifuged 15 min at 4 °C (15000 rpm) and then the supernatants were collected and IL-1β, IL-6 and TNF-α were quantified by ELISA method [24,25].…”
Section: Measurement Of Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…After serum or supernatant loading into the wells and incubation, the next step is washing which followed by second antibody addition to the reaction mixture which results in ELISA sandwich formation and then yellow color generated after the addition of stop solution. Finally, the reaction color development in wells is measured at 450 nm by ELISA plate reader [25,26].…”
Section: Measurement Of Pro-inflammatory Cytokinesmentioning
confidence: 99%